Cohort-friendly protocol for the determination of two urinary biomarkers of exposure to pyrethroids and neonicotinoids using gas chromatography-triple quadrupole mass spectrometry - Charisiadis, Pantelis; Delplancke, Thibaut; Makris, Konstantinos C. (My University, 2019)
Neonicotinoids (NEOs) and synthetic pyrethroids (PYRs) are active ingredients of commercial pesticides and/or insecticides with extensive indoor and outdoor applications, worldwide. Improved exposure metrics are warranted for NEOs and PYRs, if we are to better understand their human health effects. A cohort-friendly protocol for determining non-specific biomarkers of exposure to NEOs and PYRs, e.g. 6-chloronicotinic acid (6-CN) and 3-phenoxybenzoic acid (3-PBA), respectively, in human urine voids was proposed. A series of optimization experiments were conducted to validate the bioanalytical protocol using gas chromatography coupled with triple quadrupole mass spectrometry (GC-QqQ-MS/MS) in MRM mode. The method reached low detection limits for both analytes (0.075 μg L−1 for 6-CN and 0.050 μg L−1 for 3-PBA) in a short preparation and analysis time. The method used small initial urine sample volume (2 mL), short extraction time (≈ 240 min for the batches of 32 samples) and instrumental analysis time (≈ 14 min) for both pesticide metabolites in a single run. This protocol could facilitate the assessment of population exposure metrics for these pesticides and their inclusion in health risk assessment. [Figure not available: see fulltext.].
Keywords: 3-Phenoxybenzoic acid; 6-Chloronicotinic acid; Cohorts; Exposure; Metabolites; Neonicotinoids; Pesticides; Pyrethroids